Ottoman wrecks of the Black Sea - Batchvarov, Kroum (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The Black Sea Maritime Archaeology Project documented at least 36 shipwrecks dating to the period of Ottoman dominance. About half the vessels were of one- and two-masted sailing merchant ships. Though broadly similar, there are significant variations between them within the common shipbuilding tradition. The sites provide us with unique view of rigs and rigging in the Ottoman Black Sea.